Relaxor behavior in multiferroic BiMn2O5 ceramics - Fier, I. [UNESP]; Walmsley, L. [UNESP]; Souza, J. A. (American Institute of Physics (AIP), 2011)
In polycrystalline BiMn2O5, a broad thermal stimulated depolarization current curve has been observed in the range from 10 K to 300 K and the pyroelectric coefficient determined. In magnetic susceptibility measurements reported in the literature, features appearing in the pyroelectric coefficient could also be identified for the same temperatures, suggesting a connection between electric and magnetic data above the Neel temperature. A detailed study of the dielectric constant from 240 K to 700 K for an extended range of frequencies revealed a broad maximum at low frequencies, characteristic of relaxor ferroelectrics, following Vogel-Fulcher relation. A freezing temperature of the polar nanoregions T-f = 512 K has been determined. This high temperature ferroelectric behavior is attributed to the Bi3+ in the distorted BiO8 cage. (C) 2011 American Institute of Physics. [doi:10.1063/1.3650455]